(3GdYbO GdaGNQ GdMSf aj WHbGJ CYjGf Gdjefs - (3GdNRQLj , ehab GdOjf CHh GdMSf,J (B812 (3g` s
(3ChdgG (B:s
(3Chd HGH GdXGA GdeYLeI hgh GdHGH GdSGHY YTQ s
(3BNQgG (B:s
(3GdHGH GdKdGKhf hgh HGH GdfSGA s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B274 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B61s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B238 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B184 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeJMa GdHQjWGfi (B(kings college 72) s
Keywords: (3GdJGQjNs